Feminist Collections, v.28, no.2 (winter 2007) - (:unkn) unknown (My University, 2007)
Subtitle: A Quarterly of Women's Studies Resources. 46p.
FROM THE EDITORS. BOOK REVIEW: Working-Class Women in Higher Education, by Frances M. Kavenik. A RESEARCH REVOLUTION IN THE MAKING: Google Books and More as Sources for Women’s History, by Phyllis Holman Weisbard. FEMINIST VISIONS: From Girl Power to Empowerment: The Theory, Pedagogy, and Practice of Girls’ Film, by Sarah Hentges. Is “Education” the Answer? Films about Human Rights and Social Imbalances in India, by Heidi Fischle. E-SOURCES ON WOMEN & GENDER. NEW REFERENCE WORKS IN WOMEN'S STUDIES. RESOURCES ON YOUNG ADULT LITERATURE: By Phyllis Holman Weisbard & Nicole Grapentine-Benton. PERIODICAL NOTES. ITEMS OF NOTE. BOOKS RECENTLY RECEIVED.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews; Working Class Women in Higher Education; Google Books; Girls' Films; Women in India; Young Adult Literature; E-Sources